2007
DOI: 10.1185/030079908x253438
|View full text |Cite
|
Sign up to set email alerts
|

Rivastigmine exposure provided by a transdermal patch versus capsules

Abstract: The analyses were consistent with previous reports of a markedly less fluctuating, more continuous drug delivery with the rivastigmine patch. This characteristic delivery profile is associated with similar efficacy yet improved tolerability, compared with capsules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 10 publications
1
56
0
2
Order By: Relevance
“…Разработка пластыря с ривастигми-ном стала возможной благодаря низкой молекуляр-ной массе, а также жиро-и водорастворимым свой-ствам молекулы, что способствовало свободному поступ лению препарата через кожу и гематоэнцефа-лический барьер [11]. Благодаря снижению пика до-зы и меньшему влиянию при трансдермальном вве-дении на циркадный ритм выработки холинэстера-зы, применение ТТС с ривастигмином почти на 2 / 3 позволило снизить частоту гастроинтестинальных побочных эффектов по сравнению с пероральным приемом, при сопоставимом клиническом эффекте [12][13][14].…”
Section: базисная терапияunclassified
“…Разработка пластыря с ривастигми-ном стала возможной благодаря низкой молекуляр-ной массе, а также жиро-и водорастворимым свой-ствам молекулы, что способствовало свободному поступ лению препарата через кожу и гематоэнцефа-лический барьер [11]. Благодаря снижению пика до-зы и меньшему влиянию при трансдермальном вве-дении на циркадный ритм выработки холинэстера-зы, применение ТТС с ривастигмином почти на 2 / 3 позволило снизить частоту гастроинтестинальных побочных эффектов по сравнению с пероральным приемом, при сопоставимом клиническом эффекте [12][13][14].…”
Section: базисная терапияunclassified
“…Pharmacokinetic studies have shown that transdermal administration of rivastigmine prolongs the time to reach the peak concentration and reduces fluctuations in plasma concentration. It is these differences in peak and trough plasma concentrations that are in part responsible for the decreased side effects associated with the patches in comparison to the capsules [Mercier et al 2007;Cummings et al 2007]. Unlike other acetylcholinesterase inhibitors, rivastigmine is largely interaction free.…”
Section: Dementiamentioning
confidence: 99%
“…Innovations in transdermal delivery systems (TDS) have made important contributions to medical practice by providing advances in the delivery of treatment with existing and novel drugs. TDS have significant advantages (see Table 1) over other routes of administration, such as providing prolonged and steadier drug levels [Mercier et al 2007], the ability to interrupt treatment abruptly by removing the patch and less frequent dosing. Drug delivery through skin means avoidance of gastrointestinal incompatibility and hepatic first pass metabolism, without the unpleasant and painful experiences with injections or rectal applications.…”
Section: Introductionmentioning
confidence: 99%
“…19 The pharmacokinetic rationale and clinical data supporting the development of the rivastigmine patch is discussed in more detail by Frölich elsewhere in this issue of European Neurological Review. 20 The rivastigmine patch allows easy access to the therapeutic dose, with a simple one-step dose increase from the starting dose patch (4.6mg/ 24-hour) to target-dose patch (9.5mg/24-hour).…”
Section: Starting Treatmentmentioning
confidence: 99%
“…21 While it has been established that the target-dose rivastigmine patch (9.5mg/24-hour) offers comparable drug exposure and similar efficacy to the maximum recommended oral dose of 12mg/day rivastigmine capsules, 19,22 the starting-dose patch (4.6mg/24-hour) provides comparable drug exposure to an oral dose of 6mg/day. 19,20 Rivastigmine oral 6mg/day has been previously demonstrated in large clinical trials to be an effective dose, 23,24 suggesting that using the rivastigmine patch allows patients to start on an effective dose straight away. Patients may derive benefit from an effective dose immediately during the titration phase of treatment, before increasing to the target-dose rivastigmine patch (9.5mg/24-hour).…”
Section: Starting Treatmentmentioning
confidence: 99%